Preparation of Surface Enhanced Raman Substrate in Microfluidic Chip and the Detection of SYBR Green I - Wu, Jian; Zhang, Tian; Wang, Chunyan; Chen, Tao (Current Nanoscience, 2017)
Background: Microfluidic chip, also known as lab-on-chip, is recognized as one of the most important advanced science and technology in twenty-first Century. Due to high chemical specificity and high information content, SERS can be used in a microfluidic channel to achieve simultaneous monitoring of composition of multiple analytes. In this paper, we present a simple method to prepare SERS substrate inside a microfluidic chip to detect SYBR Green I. Methods: A microfluidic chip was prepared by a 248 nm excimer laser. A particle-free and lowviscosity precursor solution synthesized by silver acetate, formic acid, and aqueous ammonium hydroxide was dropped in the microfluidic channel. After fifteen minutes of heating on a heating platform, Ag nanoparticles were generated in the channel of microfluidic chip. Then the SERS-based microfluidic systems was used to detect the SYBR Green I dye molecules. Results: Raman signal of SYBR Green I dye can be significantly enhanced in this system. Moreover, SYBR Green I could be quantitatively detected using this system by measuring the SERS signal. Conclusion: In this paper, a method for rapid and in situ fabrication of Ag nano materials in microfluidic chip was presented to detect SYBR Green I by SERS. This method is simple and fast. It has good research and application prospects in polymerase chain reaction (PCR) detection or biological and pharmaceutical testing.Keywords: microfluidic chip, Surface enhanced Raman, SYBR Green I, polymerase chain reaction, excimer laser, PMMA.
Keywords: SYBR Green I